Growth and Survival of Shining Barb (Pethia conchonius) Spawn in Different Stocking Density - Nanda, Chinmaya; Swain, Sambid; Pradhan, Samik Kumar; Prusty, Ajay Kumar (NG Agricultural Sciences, 2025)
This study investigated the effects of different stocking densities on the growth and survival of shining barb spawn (Pethia conchonius) in a 27-liter glass aquarium over 45 days. Each of the three stocking densities consisting of 1, 3, and 5 larvae per liter received three replicated trials. The larvae were fed with a mixed diet of zooplankton and artificial feed. Stocking density of one larva per liter resulted in the highest mean body weight together with maximum length measurements and the highest survival rate. An optimal water quality parameters were maintained identically across all the treatment. The study proved that when each spawn is placed in one liter of solution, the shining barb spawn grows best due to optimal environment conditions essential for aquaculture production, specifically fish farming. Future research can further explore the long-term effects of stocking density on fish health and development.